Transporter proteins as ecological assets and features of microbial eukaryotic pangenomes - Milner, DS; Galindo, LJ; Irwin, NAT; Richards, TA (Annual Reviews, 2023)
Here we review two connected themes in evolutionary microbiology: (a) the nature of gene repertoire variation within species groups (pangenomes) and (b) the concept of metabolite transporters as accessory proteins capable of providing niche-defining “bolt-on” phenotypes. We discuss the need for improved sampling and understanding of pangenome variation in eukaryotic microbes. We then review the functional factors that shape the repertoire of accessory genes within pangenomes. As part of this discussion, we outline how gene duplication is a key factor in both eukaryotic pangenome variation and transporter gene family evolution. We go on to outline how, through functional characterization of transporter-encoding genes, in combination with analyses of how transporter genes are gained and lost from accessory genomes, we can reveal much about the niche range, ecology, and the evolution of virulence of microbes. We advocate for the coordinated systematic study of eukaryotic pangenomes through genome sequencing and the functional analysis of genes found within the accessory gene repertoire.